2014
DOI: 10.1096/fj.14-257345
|View full text |Cite
|
Sign up to set email alerts
|

SNAIL‐induced epithelial‐to‐mesenchymal transition produces concerted biophysical changes from altered cytoskeletal gene expression

Abstract: A growing body of evidence suggests that the developmental process of epithelial-to-mesenchymal transition (EMT) is co-opted by cancer cells to metastasize to distant sites. This transition is associated with morphologic elongation and loss of cell-cell adhesions, though little is known about how it alters cell biophysical properties critical for migration. Here, we use multiple-particle tracking (MPT) microrheology and traction force cytometry to probe how genetic induction of EMT in epithelial MCF7 breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 48 publications
(64 reference statements)
9
41
0
Order By: Relevance
“…Recent studies have shown that the expression of matrix metalloproteinase (MMP) mRNAs and proteins associates tightly with diverse developmental and pathological processes, such as tumor metastasis and mammary gland involution. Snail is a transcription factor that is known to transcriptionally target MMPs during the process of EMT [25]. In the present study, pterostilbene inhibited the transcription factors ZEB1, Snail, Twist and Slug.…”
Section: Discussionsupporting
confidence: 55%
“…Recent studies have shown that the expression of matrix metalloproteinase (MMP) mRNAs and proteins associates tightly with diverse developmental and pathological processes, such as tumor metastasis and mammary gland involution. Snail is a transcription factor that is known to transcriptionally target MMPs during the process of EMT [25]. In the present study, pterostilbene inhibited the transcription factors ZEB1, Snail, Twist and Slug.…”
Section: Discussionsupporting
confidence: 55%
“…A series of studies have demonstrated that actin, microtubules, and intermediate filaments all contribute to support external compressive stresses (4)(5)(6). In accord with these studies, in a genetically engineered model of the epithelialmesenchymal transition, we recently found that mesenchymal cells could support less stress than their epithelial counterparts, which correlated with decreased polymerized actin and cytoplasmic stiffness (7). Here, we show that compressive stress is not actively supported by cytoskeletal filaments, but induces NHE1-dependent sodium efflux from the tumor cells.…”
supporting
confidence: 53%
“…Snail-induced EMT produces concerted biophysical changes due to altered cytoskeletal gene expression. Biophysical changes associated with cancer metastasis, including elevated traction forces and loss of cytoskeletal and nuclear structure, are directly induced by EMT in the absence of any extraneous environmental cues (53). Snail promotes EMT in breast cancer cells in part via activation of nuclear ERK2 (54).…”
Section: Emt Transcription Factors In Breast Cancermentioning
confidence: 99%